Nomenclature changes in Phalaenopsis subgen. Hygrochilus (Orchidaceae; Epidendroideae; Vandeae) based on DNA evidence - Li, Ming-He; Gruss, Olaf; Liu, Zhong-Jian (Phytotaxa, 2016)
The taxonomy of Phalaenopsis subgen. Hygrochilus is poorly understood, resulting in great difficulties in distinguishing and identifying infrageneric taxa. It has long been known that the plant called H. parishii has two strikingly different flowers forms, ‘parishii’ and ‘marriottiana’. An analysis of ITS nrDNA and five plastid regions (atpI-atpH, trnK-matK, trnH-psbA, trnL-F and trnS-trnM) obtains clear evidence that the ‘parishii’ and ‘marriottiana’ forms are two distinct species. Here, five species of subgenus Hygrochilus are recognized: Phalaenopsis japonica, P. marriottiana, P. subparishii, P. tigrina (the new name of H. parishii in Phalaenopsis), and P. tsii. A plate of flowers to aid in identification of the species of this group is also provided.